THE PARENTS’ PERCEPTION TOWARD ENGLISH SUBJECT OF ELEMENTARY SCHOOL IN PALEMBANG - Herlina Herlina; Hermansyah Hermansyah; Diana Luspa (Universitas PGRI Palembang, 2021)
Despite the policy of English as a subject in Indonesia’s elementary school, the process of teaching and learning English is still relevant. However, some aspects need to be considered in implementing the policy, for instance, teachers and parents’ perception. This research is intended to find out about a survey on the parents’ perception toward English subject in elementary school at Palembang. This research uses descriptive quantitative approach. The subject consists of 126 parents. The data are collected by using 5-point Liker scale questionnaires that will be distributed to teachers and student’s parents. In analyzing the data, the researcher will use descriptive statistic by calculating mean, standard deviation, and categorized the total score. As suggestions, teachers and parents’ positive perception should be complemented with their understanding of young learners’ characteristics and English for young learner’s principle. Moreover, the government should also consider teachers and parents’ perception in making future policy related to English for young learner.